Determination Of Residual Hazardous Chemical Concentrations In Pharmaceutical Chemistry Laboratory Solid Waste Using Conventional Titration Methods - Muhammad Nur Abdillah (Sean Institute, 2024)
Chemical laboratory waste often contains hazardous chemicals that can pose risks to the environment and human health if not properly managed. This study evaluates the residual chemical concentrations in solid laboratory waste from pharmaceutical chemistry labs using conventional acid-base titration methods. The objective is to determine the exposure levels of acidic and basic chemicals in solid waste and assess the accuracy and precision of the analytical methods. Samples tested included filter paper, wiping cloths, and absorbent cloths, with results showing acidic chemical concentrations up to 0.998 M and basic chemical concentrations up to 0.344 M. The titration method demonstrated high accuracy with recovery percentages of 99.00% for acid addition and 99.50% for base addition, and excellent precision with RSD percentages of 0.02% and 0.04%, respectively. The study recommends separating waste based on chemical type, using appropriate absorbent materials, providing regular training for laboratory personnel, and integrating modern technology into waste management practices. These findings offer critical insights to improve laboratory waste management practices, aiming to minimize environmental impacts and health risks.